AN ANALYSIS OF MINOR FIGURATIVE LANGUAGE USED IN STAND-UP COMEDY PERFORMED BY HASAN MINHAJ ENTITLED HOMECOMING KING - Desfri Handika; Hermawati Syarif; Leni Marlina (English Language and Literature, 2019)
Figurative language is a way of delivering a message which has an unreal meaning. The use of figurative language usually found in everyday conversation, in literary works, and in public speaking. Most of the speaker stand-up comedy use figurative language in their performance. The purpose of this study is to find the types of minority majors used in stand-up comedy by Hasan Minhaj. This research is descriptive research which consists of exploring the depth of meaning in each figurative language. The researcher uses scanning techniques on the transcription of the appearance video that the researcher got from a trusted site. The results showed that minority figurative language was divided into metaphors, similes, metonymy, irony, allegory, personification and hyperbole. This study also intends to help stand-up comedy audiences in understanding the intentions and objectives of the speaker or comics with the material presented.